THE QUESTION OF FORMING CYBERSECURITY APPROACH IN THE CONTEXT OF NATIONAL SECURITY - GÜNTAY, Vahit (Cyberpolitik Journal, 2016)
Cyber threat is a unique conflict concept at cyberspace with differentiating information technologies in the context of international system. Besides, cyber threat proceeds rapidly in generating more important step than conventional based wars even nuclear deterrence. The difference in security perceptions of Cold War and Post Cold War Era has accelerated the development of this subject with changing threat parameters. States have become actors in cyberspace and that fact is a reality when correlated with other stake-holders in the cyberspace. This reality also remains to be a prominent agenda issue of international relations. When it is evaluated with these dimensions, it is a fact that cyber conflicts are real threats for modern states nowadays and serious problem area that generates disputes at the international arena. The missing subject for international relations researchers, is which theoretical approach going to be applied. The questions such as “Is it possible to apply an approach for cyber security in the context of international security?” or “What way needs to be followed?” are road maps of this study.